PENGARUH LATIHAN SQUAT JUMP DAN DEPTH JUMP TERHADAP KEMAMPUAN JUMP SERVICE ATLET PUTRA DALAM PERMAINAN BOLA VOLI PADA KLUB SMP NEGERI 2 BIREUEN - dedi saputra; Safrizal (CV Abid Abadi Jaya, 2026)
The coaching and development of volleyball athletes has not been running optimally. This is evident from the failure to achieve significant improvements in athlete abilities. This condition is influenced by the implementation of training that has not been optimal, both in terms of low athlete motivation, limited facilities and infrastructure, and coach support that has not fully supported the development of volleyball athletes' abilities. This study uses a descriptive correlational approach with a survey method. Data analysis was carried out using statistical tests, namely the Liliefors normality test and the t-test (mean difference). The results of the study showed that the t-test value (mean difference) of the effect of squat jump and depth jump training on the jump service ability of male athletes in volleyball games at the SMP Negeri 2 Bireuen Club obtained a t-count value of 7.731. Based on the results of the t-test calculation, the t-table value at a significance level of α = 0.05 with degrees of freedom (df = 9) was 1.833. These results indicate that the t-count value (7.731) is greater than the t-table value (1.833). Thus, it can be concluded that squat jump and depth jump training significantly improved the jump service abilities of male volleyball athletes at the SMP Negeri 2 Bireuen Club. Therefore, it is recommended that coaches and related parties increase athlete motivation and provide adequate training facilities and infrastructure so that athletes can carry out training programs consistently and optimally.